2020
DOI: 10.1177/2280800020928655
|View full text |Cite
|
Sign up to set email alerts
|

High bonding strength between zirconia and composite resin based on combined surface treatment for dental restorations

Abstract: Zirconia is the preferred material for dental restorations; however, dental restorations are usually affected by zirconia fractures due to chipping and delamination of the veneer ceramic. One effective solution for repairing chemically inert zirconia frameworks is to strongly chemically bond them with the composite resin via surface modification. Thus, the bonding strength between the zirconia and composite resin determines the performance of dental restoration. Herein, we investigate the shear bond strength b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The studies identified were published between 2017 and 2020. Data from the T A B L E 1 In vitro studies excluded from the second phase of the review Li et.al 2020 71 Maciel et.al 2020 72 Mendes et.al 2019 73 Nagaoka et.al 2019 74 Okada et.al 2017 75 Okutan et.al 2020 76 Omidi et.al 2018 77 Özdemir et.al 2019 78 Petrauskas et.al 2018 79 Ruyter et.al 2017 80 Saade et.al 2019 81 Saade et.al 2020 82 Saleh et.al 2019 Tabatabaei et.al 2018 90 Thammajaruk et.al 2020 91 Lümkemann et.al 2019 92 Zahoui et.al 2020 93 included studies were chronologically extracted in Table 2. Data extraction was performed using a predefined data extraction form as follows: author name, year of publication, zirconia generation, surface pretreatment method, primer, resin cement, aging procedure, bond strength values, and bonding failure mode analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The studies identified were published between 2017 and 2020. Data from the T A B L E 1 In vitro studies excluded from the second phase of the review Li et.al 2020 71 Maciel et.al 2020 72 Mendes et.al 2019 73 Nagaoka et.al 2019 74 Okada et.al 2017 75 Okutan et.al 2020 76 Omidi et.al 2018 77 Özdemir et.al 2019 78 Petrauskas et.al 2018 79 Ruyter et.al 2017 80 Saade et.al 2019 81 Saade et.al 2020 82 Saleh et.al 2019 Tabatabaei et.al 2018 90 Thammajaruk et.al 2020 91 Lümkemann et.al 2019 92 Zahoui et.al 2020 93 included studies were chronologically extracted in Table 2. Data extraction was performed using a predefined data extraction form as follows: author name, year of publication, zirconia generation, surface pretreatment method, primer, resin cement, aging procedure, bond strength values, and bonding failure mode analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Different intraoral repair techniques have been proposed for zirconia surface treatment to improve resin bonding. 7 These techniques are based on mechanical methods (e.g., grinding with bur and air particle abrasion), chemical methods (10-methacryloyloxydecyl dihydrogen phosphate [MDP] and other monomers such as 3-methacryloxypropyletrimethoxysilan [3-MPTS] 12 ) or a combined approach (e.g., tribochemical silica coating with silane primer [TBS]). 13 Several other surface treatments, such as laser irradiation and hot chemical etching, have also been explored to increase resin-to-zirconia bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Testing consists of changing the temperature frequently within the selected limits, e.g., 5–55 °C. The results from this type of test allow researchers to see if the connection may be weakened by expansion and contraction during thermal cycling [ 32 ].…”
Section: Studymentioning
confidence: 99%
“…Sandblasting might lead to crystal transition of zirconium dioxide from the tetragonal phase to the monoclinic phase, which reduces the mechanical properties of the material. Therefore, it is necessary to follow the manufacturer’s recommendations regarding pressure and grain size of abrasive materials [ 32 ]. Tribochemical silica coating is a more effective method of bonding composite materials with zirconia than the silanization process.…”
Section: Establishing Connections Between Composite Systems and Other...mentioning
confidence: 99%
See 1 more Smart Citation